2018
DOI: 10.1111/jcpe.12925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Porphyromonas gingivalis LPS and LR12 peptide on TREM‐1 expression by monocytes

Abstract: TREM-1 inhibitors such as LR12 could be interesting for the modulation of the excessive inflammatory response that occurs during periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
(48 reference statements)
1
5
0
1
Order By: Relevance
“…Our present data are also consistent with a recent in vitro study, demonstrating that the LR12 TREM-1 inhibitor LR12 could prevent monocytic activation by P. gingivalis LPS [40], as well as our earlier in vitro findings demonstrating that LP17 can reduce cytokine release by monocytes in response to P. gingivalis whole bacteria [20,21]. Moreover, an earlier study in a psoriasis model showed that TREM-1 blockade in vitro and ex vivo significantly reduced the number of Th17 cells and decreased the secretion of IL-17, suggesting that TREM-1 positively regulates Th17 responses [41].…”
Section: Discussionsupporting
confidence: 93%
“…Our present data are also consistent with a recent in vitro study, demonstrating that the LR12 TREM-1 inhibitor LR12 could prevent monocytic activation by P. gingivalis LPS [40], as well as our earlier in vitro findings demonstrating that LP17 can reduce cytokine release by monocytes in response to P. gingivalis whole bacteria [20,21]. Moreover, an earlier study in a psoriasis model showed that TREM-1 blockade in vitro and ex vivo significantly reduced the number of Th17 cells and decreased the secretion of IL-17, suggesting that TREM-1 positively regulates Th17 responses [41].…”
Section: Discussionsupporting
confidence: 93%
“…The TREM-1 inflammatory signaling pathway is stimulated by periodontal pathogens in immune cells, propagating proinflammatory responses (Bostanci et al 2011; Bostanci and Belibasakis 2012; Willi et al 2014; Dubar et al 2018). However, the regulation of the TREM-1 pathway during development of gingival inflammation in response to dental biofilm accumulation is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…TREM-1 itself is a transmembrane glycoprotein receptor of the immunoglobulin superfamily on neutrophils and monocytes (Gibot and Cravoisy 2004), which can also be secreted as a soluble protein into human body fluids through proteolytic cleavage by matrix metalloproteinases, and its putative ligand is shown to be peptidoglycan recognition protein 1 (PGLYRP1), recently associated with TREM-1 in periodontitis (Read et al 2015; Tammaro et al 2016; Nylund et al 2018). Periodontal pathogens can also regulate TREM-1 expression in immune cells in a manner that amplifies the proinflammatory responses, such as interleukin (IL)–1β (Bostanci et al 2011; Bostanci and Belibasakis 2012; Willi et al 2014; Dubar et al 2018). An important role of the TREM-1 signaling pathway is to fine-tune the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…The mRNA levels of TREM-1, not TREM-2, were significantly increased in WARS1-treated J774.1 cells in time-dependent ( Figure 2 a) and dose-dependent manner ( Figure 2 b). LPS served as a positive control [ 15 ]. Protein levels of intracellular TREM-1, as well as of the secreted soluble form, were remarkably elevated by WARS1 after 8 h treatment ( Figure 2 c).…”
Section: Resultsmentioning
confidence: 99%